2020
DOI: 10.17138/tgft(8)20-27
|View full text |Cite
|
Sign up to set email alerts
|

Dry matter concentration and corn silage density: Effects on forage quality

Abstract: Considering the hypothesis that density and dry matter (DM) concentration may be used as indicators of silage nutritional quality, the aim of the present study was to determine density and maturation stage (i.e. DM concentration) of corn silages under farm conditions in Brazil, establishing relationships between density and physical and chemical characteristics. In a completely randomized design, 20 bunkers of corn silage, each from a different farm, were used for data collection. Using a coring machine, 5 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…The high compaction could promote plant cell rupture and juice exudation and might promote LAB fermentation, quickly producing more LA and leading to a decreased pH [21]. It was found that the 800 g/L silage had a higher LA content and a lower pH than the 700 g/L and 600 g/L silages [22]. The LA/AA values of all silages were found to be above 3; this indicates that the fermentation process was predominantly homolactic [1], resulting in reduced fermentation losses, particularly in silages with high ensiling densities [23].…”
Section: Discussionmentioning
confidence: 99%
“…The high compaction could promote plant cell rupture and juice exudation and might promote LAB fermentation, quickly producing more LA and leading to a decreased pH [21]. It was found that the 800 g/L silage had a higher LA content and a lower pH than the 700 g/L and 600 g/L silages [22]. The LA/AA values of all silages were found to be above 3; this indicates that the fermentation process was predominantly homolactic [1], resulting in reduced fermentation losses, particularly in silages with high ensiling densities [23].…”
Section: Discussionmentioning
confidence: 99%